Coastal acidification impacts on shell mineral structure of bivalve mollusks. Issue 17 (14th August 2018) - Fitzer, Susan C.; Torres Gabarda, Sergio; Daly, Luke; Hughes, Brian; Dove, Michael; O'Connor, Wayne; Potts, Jaimie; Scanes, Peter; Byrne, Maria
Abstract: Ocean acidification is occurring globally through increasing CO2 absorption into the oceans creating particular concern for calcifying species. In addition to ocean acidification, near shore marine habitats are exposed to the deleterious effects of runoff from acid sulfate soils which also decreases environmental pH. This coastal acidification is being exacerbated by climate change‐driven sea‐level rise and catchment‐driven flooding. In response to reduction in habitat pH by ocean and coastal acidification, mollusks are predicted to produce thinner shells of lower structural integrity and reduced mechanical properties threatening mollusk aquaculture. Here, we present the first study to examine oyster biomineralization under acid sulfate soil acidification in a region where growth of commercial bivalve species has declined in recent decades. Examination of the crystallography of the shells of the Sydney rock oyster, Saccostrea glomerata, by electron back scatter diffraction analyses revealed that the signal of environmental acidification is evident in the structure of the biomineral. Saccostrea glomerata, shows phenotypic plasticity, as evident in the disruption of crystallographic control over biomineralization in populations living in coastal acidification sites. Our results indicate that reduced sizes of these oysters for commercial sale may be due to the limited capacity of oysters to biomineralize under acidification conditions. As the impact of this catchment source acidification will continue to be exacerbated by climate change with likely effects on coastal aquaculture in many places across the globe, management strategies will be required to maintain the sustainable culture of these key resources. Abstract : Coastal acidification from sulfate soil runoff, a widespread issue in Australasia, is being exacerbated by climate change with negative impacts for aquaculture. We apply scanning electron microscopy and electron back scatter diffraction to understand the impacts of sulfate soil acidification on oyster biomineralization. Our results indicate that reduced sizes of Sydney rock oysters for commercial sale may be due to the limited capacity of oysters to biomineralize under the sulfate soil acidification conditions.